ADP-Mediated Upregulation of Expression of CD62P on Human Platelets Is Critically Dependent on Co-Activation of P2Y1 and P2Y12 Receptors - Ronald Anderson; Annette J. Theron; Helen C. Steel; Jan G. Nel; Gregory R. Tintinger (Pharmaceuticals, 2020)
This study probed the differential utilization of P2Y1 and P2Y12 receptors in mobilizing CD62P (P-selectin) from intracellular granules following activation of human platelets with adenosine 5′-diphosphate (ADP, 100 µmol·L−1) Platelet-rich plasma (PRP) was prepared from the blood of adult humans. CD62P was measured by flow cytometry following activation of PRP with ADP in the absence and presence of the selective antagonists of P2Y1 and P2Y12 receptors, MRS2500 and PSB0739 (both 0.155–10 µmol·L−1), respectively. Effects of the test agents on ADP-activated, CD62P-dependent formation of neutrophil:platelet (NP) aggregates were also measured by flow cytometry, while phosphatidylinositol 3-kinase (PI3K) activity was measured according to Akt1 phosphorylation in platelet lysates. Treatment with MRS2500 or PSB0739 at 10 µmol·L−1 almost completely attenuated (94.6% and 86% inhibition, respectively) ADP-activated expression of CD62P and also inhibited NP aggregate formation. To probe the mechanisms involved in P2Y1/P2Y12 receptor-mediated expression of CD62P, PRP was pre-treated with U73122 (phospholipase C (PLC) inhibitor), 2-aminoethoxy-diphenyl borate (2-APB, inositol triphosphate receptor antagonist), calmidazolium chloride (calmodulin inhibitor), or wortmannin (PI3K inhibitor). U73122, 2-APB, and wortmannin caused almost complete inhibition of ADP-activated expression of CD62P, while calmidazolium chloride caused statistically significant, partial inhibition. PSB0739, but not MRS2500, caused potent inhibition of PI3K-mediated phosphorylation of Akt1. Optimal mobilization of CD62P by ADP-stimulated platelets is critically dependent on the co-activation of platelet P2Y1 and P2Y12 receptors. P2Y12 receptor activation is the key event in activation of PI3K, while activation of the P2Y1 receptor appears to create a high cytosolic Ca2+ environment conducive to optimum PI3K activity.